The effect of starvation on branched-chain 2-oxo acid oxidation in rat muscle. - Wagenmakers, A J (1984)
Oxidative-decarboxylation rates of branched-chain amino acids in rat hemidiaphragm and of branched-chain 2-oxo acids in hemidiaphragm, soleus muscle and heart slices of 110-120 g rats were increased considerably by 3-4 days of starvation, when they were calculated from the specific radioactivity in the medium. When the supply from endogenous protein degradation to the oxidation-precursor pool was severely limited by transaminase inhibitors, oxidative-decarboxylation rates of branched-chain 2-oxo acids rose significantly. Since this apparent increase was relatively larger in preparations from fed rats than from 3-days-starved rats, the differences in oxidation rates with nutritional state became less or even not significant. With rat heart the smaller dilution of the oxidation precursor pool after starvation is in accordance with the reported decrease in protein breakdown. Since protein degradation increases with starvation in skeletal muscles, we suggest that the amino acid pool arising from protein degradation is more segregated from the oxidation precursor pool in muscles from starved than from fed rats. We conclude that starvation increases branched-chain amino acid and 2-oxo acid oxidation in skeletal and cardiac muscle considerably less than has been suggested by previous studies.